Selected papers from the ALIA 2006 biennial conference - Raitt, David (The Electronic Library - Issue 4, Volume 25, 2007)
The Australian Library and Information Association 2006 Biennial Conference was held in sunny Perth from 19-22 September 2006 in the new Convention Centre overlooking the picturesque Swan River. The Conference theme click06: 'Create, Lead, Innovate, Connect, Knowledge' deliberately challenged the norm; playing with words and sounds, and asking participants to think about the library profession's role and responsibilities in coming years. The range and quality of presentations and papers was exceptional and the papers selected for this e-book provide a 'taste' of the innovative work and develop
Keywords: Libraries : Automation; Library science : Data processing